2020
DOI: 10.7554/elife.57056
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Wnts act synergistically to induce Chk1/Grapes expression and mediate G2 arrest in Drosophila tracheoblasts

Abstract: Larval tracheae of Drosophila harbor progenitors of the adult tracheal system (tracheoblasts). We showed previously that thoracic tracheoblasts arrest in the G2 phase of the cell cycle in an ATR-Checkpoint Kinase1(Chk1)-dependent manner prior to division and morphogenesis (Kizhedathu et al., 2018). Here we investigate developmental regulation of Chk1 activation. We report that Wnt signaling is high in tracheoblasts and is necessary for high levels of activated (phosphorylated) Chk1. We find that canonical Wnt … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The wnt genes exhibit sequence homology from wnt in the mouse to wingless in Drosophila . In holometabolous insects, such as flies and butterflies, accurate patterning and development are regulated by a series of gene expression patterns in tissues at specific developmental stages [ 49 ]. For example, wingless is a morphogen that acts as a short-range inducer and a long-range organizer across development in Drosophila and participates in patterning of wing discs followed by specification of wing margin-specific patterns [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The wnt genes exhibit sequence homology from wnt in the mouse to wingless in Drosophila . In holometabolous insects, such as flies and butterflies, accurate patterning and development are regulated by a series of gene expression patterns in tissues at specific developmental stages [ 49 ]. For example, wingless is a morphogen that acts as a short-range inducer and a long-range organizer across development in Drosophila and participates in patterning of wing discs followed by specification of wing margin-specific patterns [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of cell cycle phasing of tracheoblasts using FUCCI has shown that the cells are in the G1 phase at the time the embryo hatches into a larva and that the cells transition from G1-S-G2 in the first larval instar (L1). Tracheoblasts remain in G2 from the second larval instar (L2) through to mid third larval instar (L3) (32-40 h L3, ∼56 h) and divide rapidly thereafter ((Kizhedathu et al, 2018, 2020), Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the mechanisms for the activation of ATR/Chk1 during development, and the roles of these proteins therein, are less well understood. We reported recently that the ATR/Chk1 axis is co-opted during Drosophila development for inducing G2 arrest in progenitor cells (Kizhedathu et al, 2018, 2020). The current study was designed to shed light on the mechanism of activation of the ATR-Chk1 axis in this context, and to probe if it is distinct from the mechanism for DNA damage-induced activation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations